2016
DOI: 10.1016/j.neuroimage.2015.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of iron in the putamen predicts its shrinkage in healthy older adults: A multi-occasion longitudinal study

Abstract: Accumulation of non-heme iron is believed to play a major role in neurodegeneration of the basal ganglia. In healthy aging, however, the temporal relationship between change in brain iron content and age-related volume loss is unclear. Here, we present the first long-term longitudinal multi-occasion investigation of changes in iron content and volume in the neostriatum in a sample of healthy middle-aged and older adults (N = 32; ages 49–83 years at baseline). Iron content, estimated via R2* relaxometry, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 77 publications
5
51
0
Order By: Relevance
“…Moreover, Khalil et al showed that GM atrophy (combined cortical and deep GM) was the strongest predictor of basal ganglia mean R2*, and Langkammer et al described significant negative associations between mean QSM values in DGM and normalized DGM volumes. A longitudinal study in HCs has shown that mean R2* increases over time actually preceded atrophy in the putamen but not in the caudate nucleus . These results indicate a different behavior of putamen compared with the caudate nucleus with aging, which might be aggravated under conditions of MS. Our findings similarly separate these two regions.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Khalil et al showed that GM atrophy (combined cortical and deep GM) was the strongest predictor of basal ganglia mean R2*, and Langkammer et al described significant negative associations between mean QSM values in DGM and normalized DGM volumes. A longitudinal study in HCs has shown that mean R2* increases over time actually preceded atrophy in the putamen but not in the caudate nucleus . These results indicate a different behavior of putamen compared with the caudate nucleus with aging, which might be aggravated under conditions of MS. Our findings similarly separate these two regions.…”
Section: Discussionmentioning
confidence: 94%
“…As putamen volume is expected to decrease with age (in contrast to QSM, which increases with age), 39 age effects were also examined. In controls, putamen gray matter volume was significantly negatively correlated with QSM ( r =−0.53, P <0.001) and age ( r =−0.37, P =0.015) but these relationships were not seen in CUD (QSM: r =−0.13, P =0.416; age: r =0.05, P =0.770).…”
Section: Resultsmentioning
confidence: 99%
“…For example, decline in serum BDNF levels have been shown to predict hippocampal but not caudate volume decline in older adults [Erickson et al, ]. Likewise, brain iron accumulation has been shown to predict putamen but not caudate volume decline in late life [Daugherty and Raz, ], again suggesting that volume decline in deep gray matter may be influenced by unique physiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%